Pengembangan Multimedia Pembelajaran Berbasis PMRI untuk Meningkatkan Kemampuan Numerasi Siswa - Fitri Ma’rufah; Riawan Yudi Purwoko; Erni Puji Astuti (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The purpose of this study was to develop and determine the validity, practicality, effectiveness of PMRI-based mathematics learning multimedia to improve students' numeracy skills. This study uses a type of research and development (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques in this study were carried out by interviews, questionnaires, and tests. The instruments used include validation sheets of multimedia mathematics learning assessments by experts to measure validity, student response questionnaires to measure practicality, and evaluation test results to measure effectiveness. The subjects in this study were fifth grade students of MI Salafiyah Wareng. The data analysis technique used is validity analysis, practicality analysis, and effectiveness analysis. The results of the validity analysis from the assessment of material experts and media experts obtained an average of 3.19 with valid criteria. The practicality analysis of the student response questionnaire obtained a percentage of 83.07% with practical criteria. Analysis of the effectiveness of the student's numeracy ability test obtained a percentage of 92.31% with very good criteria. Based on the research results, this mathematics learning media is stated to be valid, practical, and effective. Thus it can be concluded that PMRI-based mathematics learning multimedia is appropriate for use in learning and can or has the potential to improve students' numeracy skills.